1904
DOI: 10.1136/bmj.1.2252.477
|View full text |Cite
|
Sign up to set email alerts
|

The Causes and Treatment of Chronic Rheumatism

Abstract: vasomotor system and also upon the nervous control of the production of heat. The dilatation of the cutaneous vessels, the increased perspiration and the cooling thereby produced are well known. The temperature of the subject may be lowered although he himself feels warmer; this is due to the warm blood which flushes the cutaneous nerves where the sensations of temperature arise. In large doses alcohol paralyses the nervous control of temperature. The man who is " dead drunk " resembles a coldblooded animal; e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

1919
1919
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…He properly noted that men have more localized symptoms (pain) and signs (tender points) given that recent data have shown that men have fewer pain symptom sites and tender points than women [59,60]. Traut [57] discredits Stockman's [32] histologic observations, stating that such findings "had little substantiation." His important contribution was to bring into focus the systemic features of FMS (eg, fatigue, poor sleep, headache, and colitis).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…He properly noted that men have more localized symptoms (pain) and signs (tender points) given that recent data have shown that men have fewer pain symptom sites and tender points than women [59,60]. Traut [57] discredits Stockman's [32] histologic observations, stating that such findings "had little substantiation." His important contribution was to bring into focus the systemic features of FMS (eg, fatigue, poor sleep, headache, and colitis).…”
Section: Discussionmentioning
confidence: 85%
“…In the same year, Stockman [32] reported patchy inflammatory hyperplasia, fibroblast proliferation, serofibrinous exudates, thickening of nerves and blood vessel walls, and capillary proliferation on biopsies of excised myalgic nodules. His findings subsequently could not be confirmed [33][34][35][36], but he provided a pathologic basis for Gower's [7•] fibrous inflammation theory.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Quintner, Bove and Cohen stated that the objective of their recent paper "A critical evaluation of the trigger point phenomenon" (Quintner et al 2014) (Dommerholt et al 2006, Gerwin et al 2004, Simons 1975, Simons 1976, since British physician Balfour in 1816 described muscle pain as "patients having a large number of nodular tumours and thickenings which were painful to the touch, and from which pains shot to neighboring parts" (Stockman 1904). We appreciate Quintner et al's efforts to critically review the current hypothetical constructs of myofascial pain and TrPs and to offer alternative perspectives and hypotheses, which eventually may lead to a better understanding of myofascial pain, although we disagree with many of their specific comments.…”
Section: Introductionmentioning
confidence: 99%